The bioglass as calcium phosphate-boron carbide for osseous filling - Zurita Da Silva, J. C.; Novaki, L.; Tsai, H. I.; Costa, E.; Pereira, L. T.P.; Andrade, A. V.C.; Borges, C. P.F.; Antunes, S. R.M.; Marques, M. B.; Bressiani, J. C.; Cruz, A. C.C.; Santos, F. A.; et al. (My University, 2004)
A bioglass with composition 12%Na2O-28%CaO-50%SiO 2-10%P2O5, combined with boron carbide(B 4C), was prepared to form foam-glass. The bioglass were prepared from pure oxides and fused in an electric furnace, at 1450°C for 3h, and melt was quenched in water, obtaining a non-crystalline material. The bioglass and bioglass+B4C, were characterize by X-ray fluorescence analysis showing the stoichiometric composition in a bioactive region of phase diagrams. The bioglass and bioglass+B4C showed the lower density in foam-glass form, and had the bioactivity characteristic in a simulate body fluid (SBF) and blood suspensions in-vitro assays.